"I feel that life is meaningless": Vietnamese adolescents' experiences of and reflections about interpersonal violence. (3rd April 2018) - Le, M. T. H.; Holton, S.; Kirkman, M.; Fisher, J.
Abstract : Background: The experiences of and reflections on interpersonal violence and victimisation among adolescents living in low- and middle-income countries are poorly understood. The aim was to describe Vietnamese adolescents' reflections on their experiences of victimisation. Method: A self-completed, cross-sectional survey investigating exposure to violence among high school students in Hanoi, Vietnam was conducted during 2013–2014. The last section invited participants to write about any of the matters covered in the questionnaire. Thematic analysis was conducted on these free-text comments. Results: A total of 73/76 eligible students participated in the pilot and 1616/1745 in the main survey. Of these, a total of 239 records with free-text comments were analysed. Students described experiences of violence occurring at home, at school and in the community. Experiences of violence led to sadness, loneliness, having extremely negative thoughts about the value of life, and suicidal ideas. Adolescents' experiences occurred in the context of poor parent–adolescent and teacher–student relationships, particularly concerning dissatisfaction with academic performance. Adolescents wanted to be trusted, to be given more autonomy, and to improve their relationships with parents and teachers. Conclusions: Vietnamese adolescents experience various forms of victimisation, which are detrimental to their health and wellbeing. Understanding of their experiences of and perceptions of violence and its impact on their health and wellbeing is important in the prevention of violence against young people in Vietnam.